1982
DOI: 10.1111/j.1399-0004.1982.tb01378.x
|View full text |Cite
|
Sign up to set email alerts
|

The dermatoglyphic pattern of the Kabuki make‐up syndrome

Abstract: Dermatoglyphic analyses of 12 patients with the newly recognized Kabuki make-up syndrome revealed a combination of unusual dermatoglyphic patterns. They included frequent fingertip ulnar loop patterns (72%), the absence of digital triradius c or d (25%), an interdigital triradius bc or cd (33%), hypothenar loop patterns (67%), and ulnar loop patterns in the fourth interdigital area (17%). Other unusual findings included persistence of fingertip pads (58%), a single flexion crease of the fourth or fifth finger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…1,2 The recovery period here was similar to the case of Lincoff et al, 3 where inadvertent intraocular injection of lidocaine showed improvement in retinal function 4 h later and recovery in 16 h. This is rare but can occur especially in cases of communication with the posterior segment, for example, ruptured posterior capsule and aphakia, where anaesthesia can diffuse readily into the vitreous cavity coming into direct contact with the retina and optic nerve. Visual recovery is complete with no apparent functional damage.…”
Section: Commentsupporting
confidence: 61%
“…1,2 The recovery period here was similar to the case of Lincoff et al, 3 where inadvertent intraocular injection of lidocaine showed improvement in retinal function 4 h later and recovery in 16 h. This is rare but can occur especially in cases of communication with the posterior segment, for example, ruptured posterior capsule and aphakia, where anaesthesia can diffuse readily into the vitreous cavity coming into direct contact with the retina and optic nerve. Visual recovery is complete with no apparent functional damage.…”
Section: Commentsupporting
confidence: 61%
“…TABLE I. Conditions known to be associated with prominent fetal pads [Niikawa et al, 1982;Thompson et al, 1987;Teebi et al, 1989;Hennekam et al, 1990;Romano et al, 1994;Lo et al, 1998;Lukusa and Fryns, 1998;Wilson, 1998;Bertola et al, 1999;de Vries et al, 2000;Forrester et al, 2001;Lukusa et al, 2001;Galan-Gomez et al, 2004;Grossfeld et al, 2004;Oudesluijs et al, 2005;Prescott et al, 2005;Salpietro et al, 2005;Tyson et al, 2005;Lalani et al, 2009;Reddy et al, 2009;Shimojima et al, 2009]. …”
Section: Discussionmentioning
confidence: 97%
“…The described dermatoglyphic patterns refer to the dermal crests on the toes, palms and soles of the feet (NASSAU et al, 2006). In Kabuki Syndrome, some of the described patterns are frequent, such as the attenuation and/or absence of the distal interphalangeal (DIP) flexion crease on the third and fourth joint of fingers, which limits movement and flexibility of the joints; increase in the hypotanar pattern (musculature in the palm below the fifth phalanx) and increase in ulna loops (NIIKAWA et al, 1982). Finger pad conformation is not only associated to Kabuki Syndrome, since the occurrence rate (gene penetration with expressivity) in the normal population is 3% (JONES et al, 2013).…”
Section: Discussionmentioning
confidence: 99%